Team composition in epee fencing which accounts for sportsmen`s individual performance - Zadorozhna, O.; Briskin, Y.; Perederyi, A.; Pityn, M.; Sydorko,O. (Journal of Physical Education and Sport, 2018)
The research was devoted to team composition in epee fencing with accounting of sportsmen`s individual performance. Analysis of the literature enabled to reveal that one of the ways of improvement of the quality of fencers training process and their achievements in team competitions is the substantiation of team forming with accounting results of bouts at different positions during team matches. Problem and aim. The issue of team formation in fencing is mentioned fragmentally, which points at absence of substantiated approaches in its realization at different stages of team competitions. There is the need for deep analysis of athletes` results in the bouts with various opponents and their comparison at different positions. Methods. Theoretical analysis and synthesis, analysis of documentary material, comparison, abstraction, methods of induction and deduction, pedagogical observation, methods of mathematical statistics. Results and Conclusions. For the solvation of the set tasks the sequence of athletes` performance in team competitions and their effectiveness depending on the serial number of the performance were analyzed. The protocols of the competition for the 2016-2017 season were used for assessment of athletes` performance of national teams such as Estonia, China, Korea. For assessment of Ukrainian team performance there were analyzed the results of all competitions during the 2016-2017 season. It was revealed that at the present stage of epee fencing there are used five approaches of team forming with accounting of sportsmen`s individual performance. They are substantiated by results of athletes` performance at different positions.